The The Effect of Imposing Final Income Tax and Tax Sanctions on the Motivation to Pay Taxes of E-Commerce MSME Entrepreneurs (Case Study of E-Commerce MSME in the Cemara Asri Complex) - Salim Santoso, Devitasari; Tri Wulandari (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine the effect of the imposition of final income tax and tax sanctions on the motivation to pay taxes on E-Commerce MSME entrepreneurs (Case Study on E-Commerce Micro, Small and Medium Enterprises in the Cemara Asri Complex). This study uses quantitative data types and data sources are primary data sources. The population in this study were 117 E-Commerce UMKM located in the Cemara Asri Complex. The sample in this study amounted to 47 E-Commerce MSMEs using purposive sampling data collection techniques. Data analysis and testing consists of validity test, reliability test, descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (T test) and simultaneously (F test), and determination coefficient test. These results show that Final Income Tax has a significant effect on Motivation to Pay Taxes with a t value of 4.944> T table 2.014. Tax Sanctions have no effect and are not significant to the Motivation to Pay Taxes with a t value of 0.292 < T table 2.014. Final Income Tax and Tax Sanctions have a significant effect on Motivation to Pay Taxes with a calculated F value of 27.819> F table value of 3.21 and a regression coefficient value of 55.8%.